Design of Three-Level NPC AC/DC Bidirectional Converter Using Model Predictive Controller for DC Bus Voltage Stability of Subway - Mohsin Ihsan; Shunfeng Yang (Engineering Proceedings, 2023)
In this paper, the model predictive control technique is proposed to control the voltage balancing for the subway train 1500 V DC system for variable loads. This paper compares the conventional neutral point clamped converter (NPC) using the control technique of a PI controller with model predictive control in variable load conditions. MPC enhances the stability of the system during variable loads in comparison with the conventional technique. Consequently, the suggested control technique using MPC can maintain the DC bus output voltage dynamics at variable loads for the subway. Simulation results are provided to demonstrate the accuracy of the DC bus output voltage dynamics for the proposed control method.